2009
DOI: 10.3748/wjg.15.5563
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound and magnetic resonance imaging forre-staging rectal cancer after radiotherapy

Abstract: AIM:To compare the sensitivity and specificity of two imaging techniques, endoscopic ultrasound (EUS) and magnetic resonance imaging (MRI), in patients with rectal cancer after neoadjuvant chemoradiation therapy. And we compared EUS and MRI data with histological findings from surgical specimens. METHODS:Thirty-nine consecutive patients (51.3% Male; mean age: 68.2 ± 8.9 years) with histologically confirmed distal rectal cancer were examined for staging. All patients underwent EUS and MRI imaging before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 30 publications
2
28
0
6
Order By: Relevance
“…EUS should be strongly considered for T staging of rectal cancers [12]. Mezzi et al [13 ]concluded that EUS and MRI are accurate imaging techniques for staging rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…EUS should be strongly considered for T staging of rectal cancers [12]. Mezzi et al [13 ]concluded that EUS and MRI are accurate imaging techniques for staging rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A szakirodalomban a re-staging pontossága a T-stádi-um tekintetében széles határok között mozog (27-75%) [1,[7][8][9][10][11][12][13][14][15][16][17]. Marone és mtsai 6 éves periódusban hasonlí-tották össze az előrehaladott rectumtumorok stagingjé-nek és a neoadjuváns kezelést követő re-stagingjének RUH pontosságát 85 beteg bevonásával.…”
Section: áBraunclassified
“…A T-staging során tapasztalt jó eredmények (86%) CRT után jelentő-sen romlottak (61%), míg N-staging esetén a pontosság érdemben nem változott (58%, illetve 59%) [9]. Pastor és mtsai 7 éves prospektív tanulmányában 54%-os egyezést írtak le a patológiai T-stádiummal [10], míg Mezzi 39 beteg vizsgálatakor csupán 46%-os, Vanagunas pedig 82 beteg vizsgálata során 48%-os pontosságot állapított meg, az esetek 38%-ának túlbecslésével [11,12]. Huh és mtsai tanulmányukban [13] ennél is alacsonyabb (38,3%) pontosságot állapítottak meg előrehaladott rectumcarcinomák neoadjuváns kezelést követő re-stagingjekor a Tstádium tekintetében.…”
Section: áBraunclassified
See 1 more Smart Citation
“…(52)(53)(54) . No presente estudo, com o objetivo de propiciar a melhor análise da invasão de lesões na parede do reto sem a influência de fatores que pudessem gerar viés para a avaliação, optou-se por incluir apenas pacientes que não realizaram terapia neoadjuvante.…”
Section: Decisão Terapêuticaunclassified